The Ability to Form a Brand of The Tourist Destination of Bukhara Based on The Existing Image - Bozorova Sitora Kodirovna (Research Parks Publishers, 2021)
The article discusses the ability to form a brand of the tourist destination of Bukhara based on the existing image. As well as products and services, tourism areas are leaving the global tourism market in the same historical period, when the number of travel destinations offering similar types of travel is growing, becoming more and more global with their own brand